EVALUASI PROGRAM KELUARGA HARAPAN (PKH) PADA SISWA SMP - Rahmat Diyanto; Darsono Darsono; Eddy Purnomo (Faculty of Teacher Training and Education, University of Lampung, 2015)
This research aimed to evaluate the Program Keluarga Harapan (PKH) to Junior High School students and specifically aims to analyze: the condition of the needs of the PKH student participants, the facilities and infrastructure that support the learning process, the implementation result of the program in helping the learning process, and the achievement of the results of the implementation of the Program Keluarga Harapan (PKH) in Junior High School students. This type of research is categorized as evaluation research of the model CIPP (Context, Input, Process and Product) and used analytical testing chi-square test. Evaluation result showed that the Program Keluarga Harapan (PKH) in Junior High School students work well where the implementation of the Program PKH provided by the government in tackling the problem of poverty had an impact on the students' progress in helping the success 9 years compulsory minimum.Penelitian ini bertujuan untuk mengevalusi Program Keluarga Harapan (PKH) pada siswa SMP dan secara khusus bertujuan untuk menganalisis: kondisi kebutuhan siswa peserta PKH, sarana dan prasarana yang mendukung dalam proses pembelajaran, proses pelaksanaan program dalam membantu proses belajar, dan pencapaian hasil pelaksanaan Program Keluarga Harapan (PKH) pada siswa SMP. Jenis penelitian ini dikategorikan sebagai penelitian evaluasi model CIPP (Context, Input, Process dan Product) dengan menggunakan pengujian analisis kuantitatif. Hasil evaluasi menunjukan bahwa Program Keluarga Harapan (PKH) pada siswa SMP berhasil dengan baik dimana pelaksanaan Program PKH yang diberikan oleh pemerintah dalam menanggulangi masalah kemiskinan membawa pengaruh terhadap kemajuan belajar siswa dalam membantu mensukseskan wajib belajar minimal 9 tahun.Kata kunci: contexs, input, process, product, program pkh